Ecological services of agroforestry systems in selected upland farming communities in the Philippines - Romnick Baliton; LEILA LANDICHO; Rowena Esperanza Cabahug; ROSELYN F. PAELMO; Kenneth Laruan; Ramil Rodriguez; ROBERTO G. VISCO; ARNOLD KARL A. CASTILLO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Baliton RS, Landicho LD, Cabahug RED, Paelmo RF, Laruan KA, Rodriguez RS, Visco RG, Castillo AKA. 2020. Ecological services of agroforestry systems in selected upland farming communities in the Philippines. Biodiversitas 21: 707-717. A study was conducted in three selected upland farming communities in Nueva Vizcaya, Benguet and Quezon, Philippines to assess the ecological services of agroforestry systems. Results showed that alley cropping was the dominant agroforestry system in Nueva Vizcaya, while vegetable-based and coffee-based multistorey systems were found prevailing in Benguet and Quezon provinces. Agrobiodiversity assessment revealed that the values of Shannon-Wiener diversity index of agroforestry systems in the three study sites were considered to be low to moderate, ranging from 2.21 to 2.71. This validates that the number of individuals per species in the agroforestry landscape was not evenly distributed. The means of biomass in the three study sites, ranging from 106.22-127 tons ha-1, were higher than that of agroforestry systems (102.80 tons ha-1) in the Philippines. The agroforestry systems in Nueva Vizcaya had the largest carbon stock of 57.15 ton C ha-1, followed by Quezon 52.96 ton C ha-1 and Benguet 47.80 ton C ha-1. These results are comparable to the overall mean of carbon stock of tree plantations (59.0 ton C ha-1) and higher than that of agroforestry systems in the Philippines, i.e., 45.4 ton C ha-1. Therefore, this article argues that the different agroforestry systems provide ecological services in the upland farming communities in the Philippines.